A General Strategy for Antimony‐Based Alloy Nanocomposite Embedded in Swiss‐Cheese‐Like Nitrogen‐Doped Porous Carbon for Energy Storage. (20th January 2021) - Yang, Tao; Zhong, Jiasong; Liu, Jianwen; Yuan, Yongjun; Yang, Dexin; Mao, Qinan; Li, Xinyue; Guo, Zaiping
Abstract: Due to its suitable working voltage and high theoretical storage capacity, antimony is considered a promising negative electrode material for lithium‐ion batteries (LIBs) and has attracted widespread attention. The volume effect during cycling, however, will cause the antimony anode to undergo a severe structural collapse and a rapid decrease in capacity. Here, a general in situ self‐template‐assisted strategy is proposed for the rational design and preparation of a series of MSb (M = Ni, Co, or Fe) nanocomposites with MNC coordination, which are firmly anchored on Swiss‐cheese‐like nitrogen‐doped porous carbon as anodes for LIBs. The large interface pore network structure, the introduction of heteroatoms, and the formation of strong metalNC bonds effectively enhance their electronic conductivity and structural integrity, and provide abundant interfacial lithium storage. The experimental results have proved the high rate performance and excellent cycling stability of antimony‐based composite materials. Electrochemical kinetics studies have demonstrated that the increase in capacity during cycling is mainly controlled by the diffusion mechanism rather than the pseudocapacitance contribution. This facile strategy can provide a new pathway for low‐cost and high‐yield synthesis of Sb‐based composites with high performance, and is expected to be applied in other energy‐related fields such as sodium‐/potassium‐ion batteries or electrocatalysis. Abstract : The MSb (M = Ni, Co, or Fe)/Swiss‐cheese‐like nitrogen‐doped porous carbon composites with MNC coordination prepared by a general in situ self‐templating method exhibit high rate performance and excellent cycling stability for lithium‐ion batteries. The increase in capacity during the repeated cycling process is mainly due to the ion‐diffusion mechanism, not the pseudocapacitance.